Preliminary results of acute Achilles tendon rupture treated with platelet-rich plasma and immobilization - Batista , Jorge; Quesada, Agustin; Pereira, Hélder Miguel Duarte; casola, leandro; Joannas, Germán Matías-; Arrondo, Guillermo (Journal of the Foot & Ankle, 2024)
Objective: Evaluate preliminary functional results, return to sport, re-rupture rate of acute Achilles rupture treated with one application of platelet-rich plasma (PRP), and immobilization. Methods: A prospective analytical study was performed in patients with acute Achilles tendon rupture treated conservatively, associated with a single local application of PRP within 10 days of injury. The sample comprised 28 patients diagnosed and monitored by the same team for a minimum of 12 months. The American Foot and Ankle Society Functional Rating Scale (AOFAS), Achilles tendon total rupture score (ATRS), visual analog scale (VAS), and Achilles tendon resting angle (ATRA) were evaluated, the time of return to sports activities and isokinetic strength were evaluated at the different follow-up times and injury site using magnetic resonance imaging. Results: The variance analysis of the AOFAS, ATRA, and VAS scores showed a significant difference at six and 12 months regarding the initial score and according to the injury site. The mean time to return to sports activities was 197 days, 85.7% had homogeneous tendons, and heel-rise type 2 was achieved in 28.6% at six months and 60.7% at 12 months. Conclusion: The protocol proposed by our study for Achilles tendon rupture significantly improved all the scores evaluated compared to the initial condition and the isokinetic evaluations, obtaining even better results in proximal injuries. Level of Evidence IV; Therapeutic studies investigating the results of treatment; Case series.